2014
DOI: 10.1007/s00405-014-3436-1
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on skin complications of bone-anchored hearing aids in relation to surgical techniques

Abstract: A systematic review to study the skin complications associated with the bone-anchored hearing aid in relation to surgical techniques. The following databases have been searched: MEDLINE, EMBASE, the Cochrane Library , Google scholar and the PubMed. The literature search date was from January 1977 until November 2013. Randomised controlled trials and retrospective studies were included. Initial search identified 420 publications. Thirty articles met the inclusion criteria of this review. The most common surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 32 publications
5
35
0
Order By: Relevance
“…In addition, only four (2.9 %) of all identified implants in adults placed during the study period had to be excluded. The combination of this very low exclusion rate and a presence of (adverse) soft tissue reaction that is comparable with other studies, though for dermatome technique somewhat lower, [16] suggests a representative sample.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In addition, only four (2.9 %) of all identified implants in adults placed during the study period had to be excluded. The combination of this very low exclusion rate and a presence of (adverse) soft tissue reaction that is comparable with other studies, though for dermatome technique somewhat lower, [16] suggests a representative sample.…”
Section: Discussionsupporting
confidence: 86%
“…In the field of the latter, both the dermatome and linear incision technique became popular in many centres. However, studies regarding the dermatome technique reported an overall higher rate of skin problems [3537] compared to the linear incision technique [8, 19], although methodological variability could influence these outcomes and impair adequate comparison [16]. The linear incision technique is more and more used as the preferred technique in many clinics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Late complications, (1 year or more postoperative) including implant or wire extrusion, dislocation of transducer/coupler assembly and loss of coupling (e.g., increase in in situ thresholds) need to be reported, as well as technical complications and device failures. If a revision surgery was necessary, it must be stated whether it was due to medical/ surgical (procedure) or device-related reasons [Ernst et al, 2016;Gavilan et al, 2015;Hobson et al, 2010;Lassaletta et al, 2016;Mohamad et al, 2016;Van Rompaey et al, 2011;Wazen et al, 2011;Zwartenkot et al, 2016].…”
Section: Reporting Of Surgical and Medical Characteristicsmentioning
confidence: 99%